Histologic grade and STAS as key predictors of distant recurrence in resected early-stage lung adenocarcinoma: a single-center study - Bonis, Alessandro; Pagliarini, Giulia; Comacchio, Giovanni Maria; Mammana, Marco; Pezzuto, Federica; Verzeletti, Vincenzo; Pellizzer, Enrica; Berni, Alessandro; Silvestrin, Stefano; Cannone, Giorgio; Faccioli, Eleonora; Rebusso, Alessandro; et al. (Frontiers in Oncology, 2025)
IntroductionEarly-stage lung adenocarcinoma (ADC) is curable by surgical resection in most cases. However, unexpectedly, some patients experience distant disease relapse. Emerging evidence suggests that microscopic tumor characteristics may increase the risk of tumor relapse. Consequently, we aimed to test different microscopic variables to assess their association with distant recurrence (DR).Materials and methodsWe retrieved all cases of radically treated stage I-IIA ADCs from 2016 to 2020. Clinical and pathological variables were assessed for their association with DR using univariable and multivariable logistic regression. An EGFR-adjusted model was also provided.ResultsA total of 259 patients were treated (214 lobectomies and 45 segmentectomies). After resection, 54 patients relapsed, 28 of whom had distant recurrences (DR). Spread through air spaces (STAS) was detected in 48% of samples, while vascular invasion (VI) was present in 53%, occurring 17% more frequently in those with DR. Tumor size was larger in patients with recurrence, with the largest tumors observed in those with local recurrence (25.5 mm in local vs. 23.5 mm in DR; p=0.028). Dedifferentiated (G3) ADCs were more prevalent in DR cases, accounting for 48% of samples. In univariate regression, surgical margins, LVI, necrosis, G3 primary tumors, and STAS were significant factors. In multivariate analysis, STAS showed a trend towards significance (p=0.07) while G3 remained decisive (p<0.01). The EGFR-adjusted model for DR yielded slightly better results (p=0.05 and p<0.01 respectively).ConclusionsDedifferentiation and partially STAS are key pathological predictor of distant recurrence in resected stage I-IIA ADCs. The contribution of LVI and tumor necrosis in DR needs to be further clarified. Tumor aggressiveness goes beyond the simple size measurement, claiming for a reassessment of risk models for recurrence after surgery.